Radio frequency field strength fluctuation due to digital conversion of television signals: a pilot study - Lane, P. Brian, author; Johnson, Thomas E., advisor; Gates, Timothy K., committee member; Zimbrick, John D., committee member (Colorado State University. Libraries, 2010)
All television stations in the United States ceased broadcasting on analog airwaves June 12, 2009 and now only broadcast in a digital format. Prior to June 12th, most stations broadcast in both analog and digital signals. The focus of this study was to determine whether this change in broadcasting affected exposures to radio frequency energies in the vicinity of Lookout Mountain in Golden, Colorado. The site, which is approximately 10 miles west of the Denver metropolitan area, is unique because there are homes located at and above the elevation of the transmitting towers with some homes located within 100 yards of the towers. There is public concern that the digital transition resulted in a significant increase in radio frequency exposure to homes. Measurements of radio frequency field strengths were taken during daylight hours at 21 locations where highest exposures were expected using an electromagnetic radiation meter. Measurements taken at the same locations before and after June 12, 2009 did not indicate a statistically significant change in radio frequency exposures and all measurements were below the Maximum Permissible Exposure (MPE) limit for the general public.
Covers not scanned.
Keywords: Digital television; Digital television -- Colorado; Television -- Receivers and reception